Legal regulations of complementary and alternative medicines in different countries - A, Ajazuddin; Saraf, Shailendra (Pharmacognosy Reviews, 2012)
Traditional medicines that formed the basis of health care throughout the world since the earliest days of mankind are still widely used and have considerable importance in international trade. Recognition of their clinical, pharmaceutical, and economic value is still growing, although this varies widely between countries and therefore regulation of exploitation and exportation is essential, together with international cooperation and coordination for their conservation so as to ensure their availability for the future. World Health Organization and European Union issued the guidelines defi ned the basic criteria for the evaluation of quality, safety, and effi cacy of herbal medicines with the goal of assisting national regulatory authorities, scientifi c organizations, and manufacturers in assessing documentation, submissions, and dossiers in respect of such products. Legislative controls in respect of medicinal plants have not evolved around a structured control model. There are different ways in which countries defi ne medicinal plants or herbs or products derived from them. The present review highlights the status of different countries adopted various approaches to licensing, dispensing, manufacturing, and trading to ensure their safety, quality, and effi cacy.
Keywords: Effi cacy; legislation; quality; safety; traditional medicines